Estimating the material properties of heel pad sub-layers using inverse Finite Element Analysis. (February 2017) - Ahanchian, Nafiseh; Nester, Christopher J.; Howard, David; Ren, Lei; Parker, Daniel
Highlights: An anatomically detailed 3D FE model of the human heel pad was developed based on MRI data. The heel pad was modelled as a tri-layer composite structure including macro-chamber, micro-chamber and skin layers. A combined ultrasound and loading device was used for compression of the same foot. The force–strain responses of the heel pad and its sub-layers under static and dynamic compression tests were used as inputs to inverse FEA, and hyperelastic and viscoelastic properties of the heel pad sub-layers were estimated. Abstract: Detailed information about the biomechanical behaviour of plantar heel pad tissue contributes to our understanding of load transfer when the foot impacts the ground. The objective of this work was to obtain the hyperelastic and viscoelastic material properties of heel pad sub-layers (skin, micro-chamber and macro-chamber layers) in-vivo . An anatomically detailed 3D Finite Element model of the human heel was used to derive the sub-layer material properties. A combined ultrasound imaging and motorised platform system was used to compress heel pad and to create input data for the Finite Element model. The force–strain responses of the heel pad and its sub-layers under slow compression (5 mm/s) and rapid loading-hold-unloading cycles (225 mm/s), were measured and hyperelastic and viscoelastic properties of the three heel pad sub-layers were estimated by the model. The loaded (under ∼315 N) thickness of the heel pad was measured from MR images and used for hyperelastic model validation. The capability of the model to predict peak plantar pressure was used for further validation. Experimental responses of the heel pad under different dynamic loading scenarios (loading-hold-unloading cycles at 141 mm/s and sinusoidal loading with maximum velocity of 300 mm/s) were used to validate the viscoelastic model. Good agreement was achieved between the predicted and experimental results for both hyperelastic (<6.4% unloaded thickness, 4.4% maximum peak plantar pressure) and viscoelastic (Root Mean Square errors for loading and unloading periods <14.7%, 5.8% maximum force) simulations. This paper provides the first definition of material properties for heel pad sub-layers by using in-vivo experimental force–strain data and an anatomically detailed 3D Finite Element model of the heel.